Detection of Smo, Gli2 and Gli3 Among Basal Cell Carcinoma Patients in Sulaimani Province. - Khidhir, Karzan Ghafur (Sulaimani Journal for Pure and Applied Sciences, 2017)
Basal-cell carcinoma (BCC hedgehog (Shh) of BCC. The specific downstream effector in the Shh pathway leading to cancer development is unclear. However in vertebrates, specific downstream effectors in the Shh signaling pathway including zinc-finger transcription factors Gli2 and Gli3 play the Shh pathway. S and controlled cell proliferation. The expression of transducers had not been reported yet in BCC skin of local patients. The aim of this study was to investigate the expression of S BCC biopsies taken from sun Five BCC skin biopsy specimens were taken from the sun which served as material for the study. RNA extracted from the samples, cDNA synthesised carried out and specific primers for each of the S genes were designed. Reverse transcription polymerase chain reaction (RT samples expressed genes for S patients in Sulaimani Province. These findings support the role of S the Shh–receptor complex. These results establish S oncogenes in skin and suggest a pivotal role for these transcription factors in the development of BCC. This method can be used in the diagnosis of BCC and fur study of downstream effectors in the Shh pathway may lead to an effective anti cancer therapy. Key Words: Basal cell carcinoma, Smo, Gli2, Gli3, RT-PCR. JZS (2017) 19 – 2 (Part-A) 1 Detection of Smo, Gli2 and Gli3 Among Basal Cell Carcinoma Patients in Sulaimani Province Department of Biology, College of Science, University of Sulaimani, Sulaimani, Kurdistan Region, Iraq. Basal cell carcinoma is the most common malignancy in humans. Although rarely metasta capable of significant local destruction and disfigurement. Skin cancer is accounting for about half of all cancers occur. BCC constitute approximately 80% of all nonmelanoma skin cancers [ in the world has been reported in Australia [2]. Exposure to ult radiation is generally accepted as the major cause of BCC and the risk of this disease is significantly increased by recreational exposure to the sun during childhood and adolescence cluding fair complexion, red or blond hair, and light eye color, influence responsiveness to but are also independent risk factors [4]; exposures to ionizing radiation, arsenic, and oral methoxsalen ave also been linked to the development of BCC[5,6] Journal homepage www.jzs.univsul.edu.iq Journal of Zankoy Sulaimani Part-A- (Pure and Applied Sciences) Abstract cell carcinoma (BCC) is the most common type of cancer in human. Sonic hedgehog (Shh) signaling pathway impairment plays a key role in the pathogenesis of BCC. The specific downstream effector in the Shh pathway leading to cancer development is unclear. However in vertebrates, specific downstream effectors in e Shh signaling pathway including smoothened, frizzled class receptor (S finger transcription factors Gli2 and Gli3 play an important role in regulating the Shh pathway. SMO, Gli2, and Gli3 family proteins are necessary for adequate and controlled cell proliferation. The expression of SMO, Gli2 and Gli3 signal transducers had not been reported yet in BCC skin of local patients. The aim of this study was to investigate the expression of SMO BCC biopsies taken from sun-exposed skin areas of patients in Sulaimani Provinc Five BCC skin biopsy specimens were taken from the sun which served as material for the study. RNA extracted from the samples, cDNA synthesised carried out and specific primers for each of the S genes were designed. Reverse transcription polymerase chain reaction (RT-PCR) analyses samples expressed genes for SMO, Gli2 and Gli3 in BCC skin biopsies taken from patients in Sulaimani Province. These findings support the role of SMO, Gli2 and Gli3 as a signa receptor complex. These results establish SMO, Gli2 and Gli3 as potent oncogenes in skin and suggest a pivotal role for these transcription factors in the development of BCC. This method can be used in the diagnosis of BCC and fur study of downstream effectors in the Shh pathway may lead to an effective anti cancer therapy.
Keywords: Basal cell carcinoma; Smo; Gli2; Gli3; RTPCR